INFLUENCE OF SYSTEMS OF BASIC TILL OF SOIL AND FERTILIZER IS ON THE PRODUCTIVITY AND QUALITY OF WHEAT WINTER IN SHORT TERM CROP ROTATIONS OF SOUTH STEPPE OF UKRAINE - Коваленко, Н. П.; Аль-Джанабі, К.Т.Б. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
On results the indexes of the productivity and quality of grain-growing products the rational growing of wheat winter is set in the short term crop rotations of droughty South Steppe of Ukraine. A favorable action is certain differentiated and with shelves and without shelves are certain tills of soil in green short term crop rotations with a vetch winter and peas and mustard white, where got the greatest quality indexes of winter wheat grain. Input of green pairs in short term crop rotations provided the increase of the productivity and receipt of the greatest indexes squirrel (12,7 %) and gluten (21,8 %) in grain of wheat winter. It isdiscovered that brings an excessive satiation over of crop rotations grain-crops to the decline of the productivity and quality indexes of agricultural produce at all systems of soil till, that it maybe to correct introduction black and green pairs. With the aim of increase and level maintenance fertility of soil in droughty South Steppe of Ukraine it is recommended to apply green short term crop rotations with a vetch winter and peas andmustard white. It is set that application of effective predecessors of agricultural cultures is in croprotations, systems of soil till and fertilizer will assist the decision of problems of necessities providing ofinternal market and stable export of agricultural produce, her quality improvement according tointernational standards